Inpatient Neurologic Consultation in Solid Organ Transplant Patients - Shah, Maulik (Seminars in Neurology, 2015)
A third of solid organ transplant recipients experience neurologic complications after transplantation. In this article the author reviews common and uncommon complications of the perioperative period including stroke and peripheral neuropathy, neurotoxicity associated with immunosuppressant medications such as calcineurin inhibitors, and opportunistic infections that target the nervous system. A careful clinical history, neurologic examination, and medication review are vital in generating a differential diagnosis that will guide diagnostic testing and decisions regarding treatment and management, and early recognition of many disorders is imperative to prevent irreversible neurologic morbidity and death.
Keywords: transplant medicine; encephalopathy; posterior reversible encephalopathy syndrome; calcineurin inhibitor toxicity; opportunistic infections